Capilliposide C from Lysimachia capillipes Restores Radiosensitivity in Ionizing Radiation-Resistant Lung Cancer Cells Through Regulation of ERRFI1/EGFR/STAT3 Signaling Pathway - Wu, Kan; Chen, Xueqin; Feng, Jianguo; Zhang, Shirong; Xu, Yasi; Zhang, Jingjing; Wu, Qiong; You, Mingliang; Xia, Bing; Ma, Shenglin (Frontiers in Oncology, 2021)
Aims: Radiation therapy is used as the primary treatment for lung cancer. Unfortunately, radiation resistance remains to be the major clinic problem for lung cancer patients. Lysimachia capillipes capilliposide C (LC-C), an extract from LC Hemsl., has been demonstrated multiple anti-cancer effects in several types of cancer. Here, we investigated the potential therapeutic impacts of LC-C on radiosensitivity in lung cancer cells and their underlying mechanisms. Methods: Non-small cell lung cancer cell lines were initially irradiated to generate ionizing radiation (IR)-resistant lung cancer cell lines. RNA-seq analysis was used to examine the whole-transcriptome alteration in IR-resistant lung cancer cells treated with or without LC-C, and the differentially expressed genes with most significance were verified by RT-qPCR. Colony formation assays were performed to determine the effect of LC-C and the target gene ErbB receptor feedback inhibitor 1 (ERRFI1) on radiosensitivity of IR-resistant lung cancer cells. In addition, effects of ERRFI1 on cell cycle distribution, DNA damage repair activity were assessed by flow cytometry and γ-H2AX immunofluorescence staining respectively. Western blotting was performed to identify the activation of related signaling pathways. Tumor xenograft experiments were conducted to observe the effect of LC-C and ERRFI1 on radiosensitivity of IR-resistant lung cancer cells in vivo. Results: Compared with parental cells, IR-resistant lung cancer cells were more resistant to radiation. LC-C significantly enhanced the effect of radiation in IR-resistant lung cancer cells both in vitro and in vivo and validated ERRFI1 as a candidate downstream gene by RNA-seq. Forced expression of ERRFI1 alone could significantly increase the radiosensitivity of IR-resistant lung cancer cells, while silencing of ERRFI1 attenuated the radiosensitizing function of LC-C. Accordingly, LC-C and ERRFI1 effectively inhibited IR-induced DNA damage repair, and ERRFI1 significantly induced G2/M checkpoint arrest. Additional investigations revealed that down-regulation of EGFR/STAT3 pathway played an important role in radiosensitization between ERRFI1 and LC-C. Furthermore, the high expression level of ERRFI1 was associated with high overall survival rates in lung cancer patients. Conclusions: Treatment of LC-C may serve as a promising therapeutic strategy to overcome the radiation resistance and ERRFI1 may be a potential therapeutic target in NSCLC.